Optimalisasi Produksi Gula Aren Curah pada Industri Rumah Tangga di Desa Pasigitan, Kabupaten Kendal - Baswara, Satsya Yoga; Widhiastuti, Ratieh; Dewi, Eko Nurcahya; Fathurrohman, Muhammad Dwilian; Ali, Noor Faqih Udin; Niam, Sufa’ah Hurumun (Jurnal Pengabdian Nasional (JPN) Indonesia, 2025)
Entrepreneurship is a crucial aspect in Indonesia in 2024. In the post-COVID-19 era, livelihoods can no longer rely solely on employers but must also be developed from the grassroots level through collaboration to create new job opportunities. This is essential to attract the interest of Indonesia's productive generation, particularly among rural communities and, more broadly, among nearby urban areas. Pasigitan Village, located in Boja Subdistrict, Kendal Regency, is a highland area with excellent agricultural potential. In addition to its agricultural products, Pasigitan Village also has side industries in the form of home-based businesses producing palm sugar, either in solid or bulk form, which holds great potential to be marketed to sugar export suppliers. Based on this, the UNNES service team aims to assist these home-based industries in obtaining the PIRT (Household Food Industry) certification. This certification includes training to help producers comply with good manufacturing practices and meet market standards, allowing their palm sugar products to be marketed more broadly and reach more distant markets. The selected method for this community service activity is socialization and assistance. The socialization will explore the palm sugar producers in Pasigitan Village who are part of the home-based industry group and familiarize them with PIRT standards. The assistance will then provide knowledge, understanding, and skills on how to achieve the PIRT standards. The goal is to address the existing problems and create a positive impact.